Respuesta :
Answer:
B) x = 2, y = 3 and z = 5.
Step-by-step explanation:
3x −2y + 4z = 20 .....A
-x + 5y+ 12z = 73 .....B
x + 3y −2z = 1 ......C
Adding B and C:
8y + 10z = 74 .... E
Multiply equation B by -3:
-3x - 9y + 6z = -3
Add this equation to A:
-11y + 10z = 17
Subtract this equation fro E:
19y = 57
y = 3.
Substitute y = 3 in equation E:
8*3 + 10z = 74
10z = 50
z = 5.
Finally substitute y = 3 and z = 5 into equation C:
x + 3(3) - 2(5) = 1
x + 9 - 10 = 1
x = 1 + 1
x = 2.
Answer:
B) x = 2, y = 3, z = 5
Step-by-step explanation:
3x −2y + 4z = 20
3(2) - 2(3) + 4(5) = 20
20 = 20
−x + 5y +12z = 73
-2 + 5(3) + 12(5) = 73
73 = 73
x + 3y −2z = 1
2 + 3(3) - 2(5) = 1
1 = 1